Towards enhancing capabilities of children of Overseas Filipino Workers to sustain resilience and mitigate vulnerabilities - Abenir, Mark Anthony D. (Philippine Journal of Social Development, 2019)
The Capabilities Approach was used in this study to understand the experiences of resilience and vulnerabilities in the lives of children of Overseas Filipino Workers (OFWs) in the Philippines. It argues that the impact of family separation on the functioning and capabilities of the children left behind must be analyzed. This will provide the context for identifying what specific human capabilities should be safeguarded to ensure that migration benefits are sustained and vulnerabilities are mitigated. Through focused ethnography, this study draws qualitative and quantitative insights from 2.446 workshop participants of ANAK (Anak ng Nangibang-bansa Aruga at Kaagapay or Nurturing and Support for the Children of Overseas Workers) held nationwide from 2011 to 2013. Three valuable capability sets were identified that reflected the voices of children of OFWs. Findings from this study can serve as a guide in crafting migration and development policies that are sensitive to meeting the needs of the program participants in particular, and left-behind children by migrating parents in general.